Malignant otitis externa: our experience - K. S., Rajaganesh; P., Venkateswaran; S., Gayathiri (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Malignant otitis externa (MOE) is a severe and potentially life-threatening infection that originates in external auditory canal. Infection begins in external auditory canal, spreading through fissure of Santorini to the surrounding structures. The clinical course is varied and outcome prediction is difficult. This review aims to explore the clinical presentation, treatment, and follow up of patient with MOE. Three patients who were known cases of type 2 diabetes mellitus (T2DM) presented to the Outpatient department with complaints of intractable otalgia and otorrhea. Some patients had cranial nerve palsy. Radiological investigations were used as adjunct for diagnosis. Clinically they were diagnosed with MOE and were treated with a 6 week course of intravenous ciprofloxacin and piperacillin-tazobactam. Response to treatment was assessed using improvement in signs and symptoms and level of inflammatory markers.